2022
DOI: 10.1007/s12310-022-09533-2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers, Stress, and the COVID-19 Pandemic: A Qualitative Analysis

Abstract: The 2020–2021 academic year brought numerous challenges to teachers across the country as they worked to educate students amidst the COVID-19 pandemic. The current study is a secondary data analysis of qualitative responses collected as part of a teacher survey to evaluate a social emotional learning curriculum implemented during the 2020–2021 academic year. The lived experiences of teachers ( N = 52) across 11 elementary schools in the Great Plains region were captured through open-ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 30 publications
4
44
0
1
Order By: Relevance
“…Video conferencing and other online resources became the new normal in the delivery of education. The technical skills of teachers in using digital tools for teaching and communication might have affected their perceptions of remote teaching, as teachers with fewer digital skills may perceive remote techniques as a burden [ 7 , 8 ], resulting in work-related stress [ 9 ]. Teachers must find time to attend to various online learning-related needs of students, and a key challenge faced by teachers has been to resolve the digital divide amongst students [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Video conferencing and other online resources became the new normal in the delivery of education. The technical skills of teachers in using digital tools for teaching and communication might have affected their perceptions of remote teaching, as teachers with fewer digital skills may perceive remote techniques as a burden [ 7 , 8 ], resulting in work-related stress [ 9 ]. Teachers must find time to attend to various online learning-related needs of students, and a key challenge faced by teachers has been to resolve the digital divide amongst students [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kotowski and colleagues (2022) found that more than a year into the pandemic, 72% of teachers they surveyed reported feeling very or extremely stressed out, 57% reported feeling very or extremely burned out, and more than half struggled to find a satisfactory work-life balance. Teachers also reported high levels of stress, burnout, and job dissatisfaction due to the challenges they faced with providing online instruction (Minihan et al, 2022;Walter & Fox, 2021), changes in teaching approaches (Robinson et al, 2022), and increased workloads during COVID-19 (Chan et al, 2021;Sokal et al, 2021). There continues to be a need to investigate teacher burnout, especially in charter schools, as the pandemic has likely exacerbated many trends prior to 2020.…”
Section: Teacher Burnoutmentioning
confidence: 99%
“…Considerable studies have explored teachers’ feelings and stress during COVID-19 ( Robinson et al, 2022 ). Against the background of COVID-19 pandemic, extra efforts are needed for daily teaching activities ( Nagasawa and Tarrant, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%